2016
DOI: 10.3847/0004-637x/824/1/21
|View full text |Cite
|
Sign up to set email alerts
|

The Impossibly Early Galaxy Problem

Abstract: The current hierarchical merging paradigm and ΛCDM predict that the~-z 4 8 universe should be a time in which the most massive galaxies are transitioning from their initial halo assembly to the later baryonic evolution seen in star-forming galaxies and quasars. However, no evidence of this transition has been found in many highredshift galaxy surveys including CFHTLS, Cosmic Assembly Near-infrared Deep Extragalactic Survey (CANDELS), and Spitzer Large Area Survey with Hyper-Suprime-Cam (SPLASH), which were the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
217
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(227 citation statements)
references
References 71 publications
(134 reference statements)
8
217
2
Order By: Relevance
“…At the highest redshifts of our sample z > 4.5, we find that the SFR follows a linear SFR ∝ M α , without an apparent turnoff at high mass. Although our sample may not be large enough to identify a turn-off, this result is comparable to Steinhardt et al (2014). Assuming that the fraction of high-mass, high SFR, dustobscured galaxies is not higher at these redshifts than for z < 4.5, a possible interpretation is that at these high redshifts the SFR quenching mechanisms are not yet fully in place.…”
Section: A Turn-off In the Sfr-m Relation: Evolution With Redshiftmentioning
confidence: 68%
“…At the highest redshifts of our sample z > 4.5, we find that the SFR follows a linear SFR ∝ M α , without an apparent turnoff at high mass. Although our sample may not be large enough to identify a turn-off, this result is comparable to Steinhardt et al (2014). Assuming that the fraction of high-mass, high SFR, dustobscured galaxies is not higher at these redshifts than for z < 4.5, a possible interpretation is that at these high redshifts the SFR quenching mechanisms are not yet fully in place.…”
Section: A Turn-off In the Sfr-m Relation: Evolution With Redshiftmentioning
confidence: 68%
“…In this context, recent studies have found that high-z galaxies may have had to form surprisingly early to account for the weakening of the exponential decline at the bright end of the LF with increasing redshift Finkelstein et al (2015). This could be achieved by an unusually early collapse with respect to standard clustering theory, or an increased star formation efficiency making the stellar-to-halo mass ratio appear to rise with increasing redshift (Steinhardt et al 2015). In order to have a significant impact on the CIB however, these effect must also be present in lower mass systems which contribute the bulk of the CIB.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…A correlation between the SFR and the stellar mass, known as the star formation main sequence (SFMS), has been found to exist for star-forming galaxies in the full range from low (z < 1; Brinchmann et al 2004) to high (z ∼ 6; Steinhardt et al 2014) redshifts. Both the slope and normalisation of the correlation are observed to change over cosmic time (e.g.…”
Section: Sfr Vs Stellar Mass Relationmentioning
confidence: 99%